Thermal resilience in embryos of Fucus guiryi from a marginal iteroparous southern population: May they cope with ongoing global warming? - Sánchez de Pedro Crespo, Raquel; Fernández Fernández, Andrea; García-Sánchez, María Jesús; Flores-Moya, Antonio; Bañares-España, Elena (European Journal of Phycology, 2019)
Canopy-forming macroalgae are experiencing severe biodiversity loss, species shifts and population decline in the face of global change. Single- and few-celled stages of their life-history are a key pole for recruitment and population persistence while being highly sensitive to environmental stress. In this work, thermal resilience of embryos of Fucus guiryi from the Strait of Gibraltar was investigated in relation to seasonal changes of actual temperature regime. To test whether seasonal maternal acclimation confers thermal resilience, embryos were isolated from plants in early/late summer and late winter, since F. guiryi produce fertile gametes across the year at this location (iteroparous). Survival, growth, development and photosynthesis were tested under control (15 ºC) and warming conditions (25 ºC). At 15 ºC, embryos showed consistent responses across seasons and exhibited higher growth and photosynthesis, greater volume and further development than at 25 ºC. Interestingly, winter embryos attained the greatest thermal resilience, showing similar survival and photosynthetic responses at both temperatures, despite lower growth and development at 25 ºC. Early summer embryos were the most heat-sensitive, showing growth and photosynthesis reductions of 75%, and 50% survival. Enhanced physiological performance of late summer embryos suggested a warm-hardiness process due to maternal acclimation, while also reflecting a detrimental effect of summer-heat accumulation when compared to the winter responses. Despite optimal to sup-optimal thermal threshold of F. guiryi embryos keeps between 23-25 ºC seasonally, the decline in physiological performance towards 25 ºC became less steep from early summer to winter. In the near future, embryos of F. guiryi might cope with projected warmer winters but strive at high temperatures during the onset of the warming season and chronic summer heat stress.
Keywords: Algas-Crecimiento-Gibraltar (Estrecho); Calentamiento global; Thermal resilience; Embryos; Fucus guiryi; Global warming